Positive Face Threatening Acts Analysis in “Purple Hearts” Movie - Nangin, Faith Courtney; Andries, Fivy; Lolowang, Imelda (Program Studi Pendidikan Bahasa Inggris, 2025)
This research aims to investigate the Positive Face-Threatening Acts (FTAs) inthe movie Purple Hearts (2022), focusing on how they were directed towardthe main character, Cassie. The study is qualitative, presenting findings indescriptive analysis. The data consists of key dialogues from the movie, whichwere transcribed and analyzed using Brown and Levinson’s (1987) politenesstheory. This research examinied how Cassie’s autonomy and social identity arechallenged throughout the film. The results indicate that Cassie frequentlyexperiences disapproval, criticism, contradictions, and restrictions on herindependence. The findings show that among the positive FTAs, there were 1instances of disagreement, 6 of criticism, 4 of contradiction, 3 of dismissal, 5of accusation, 2 of complaints, and 1 of face-saving. These FTAs shape hercharacter dynamics, highlighting conflicts, power struggles, and emotionaltension in the narrative. This research contributes to the understanding ofpragmatics in cinematic discourse and provides insights into how languagereflects interpersonal relationships in film.